2004
DOI: 10.1016/j.ejcts.2004.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute heart failure in an infant after cardiac surgery using levosimendan

Abstract: An infant, 2 months old, underwent cardiac surgery because of congenital heart defects and pulmonary hypertension. Surgery was performed in hypothermia and cardiac standstill. On the second day after surgery the infant had to be resuscitated due to a combination of acute left-ventricular failure, pulmonary vascular hypertension and a slight right-to-left-shunt. A breakthrough in the treatment was achieved by using levosimendan to improve left-ventricular function and to decrease vascular resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 10 publications
1
27
0
3
Order By: Relevance
“…Furthermore, IABP, mechanical unloading as well as other artificial support systems remain the therapies of choice in patients who have difficulty weaning from CPB. 5 Although the patients in this study, had not high EuroScore and predicted death rate, the ejection fraction performed preoperatively showed relatively low. Additionally, weaning from CPB does not depend only the patient's preoperative condition but the events occur during the operative course as well.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, IABP, mechanical unloading as well as other artificial support systems remain the therapies of choice in patients who have difficulty weaning from CPB. 5 Although the patients in this study, had not high EuroScore and predicted death rate, the ejection fraction performed preoperatively showed relatively low. Additionally, weaning from CPB does not depend only the patient's preoperative condition but the events occur during the operative course as well.…”
Section: Discussionmentioning
confidence: 95%
“…It has also a vasodilating effect, which is the result of activation of adenosine triphosphateregulated potassium (K ATP ) channels. 5 Clinical studies have confirmed the positive inotropic effect of levosimendan in patients with decompensated heart failure. 6 In this dose range, levosimendan increases heart rate, stroke volume, as well as cardiac output, while decreasing systemic, pulmonary and coronary artery vascular resistance as well as filling pressures.…”
Section: Levosimendanmentioning
confidence: 89%
“…Levo administration in pediatric patients was first reported in 2004 [13,14] . In 2006, Namachivayam et al in a retrospective review showed that Levo is an effective and safe agent in children with severe myocardial dysfunction, able to decrease concomitant catecholamine dosing [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Bei Kindern und Neugeborenen mit angeborenen Herzfehlern konnte die sichere perioperative Anwendung von Levosimendan ebenfalls nachgewiesen werden [6,100].…”
Section: Perioperativer Einsatz In Der Kardiochirurgieunclassified